2011
DOI: 10.1002/pros.21452
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing location of myeloperoxidase in the prostate: A preliminary immunohistochemical study

Abstract: We identified, for the first time, the presence of MPO at the surface of prostatic epithelial cells. In view of the pro-oxidant properties of this enzyme, further research is needed to define whether MPO contributes to the development of prostatic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Samples were divided around the median sperm count of 56.5 9 10 6 /mL of seminal plasma (below/equal median group n = 17; above median group n = 16). A recent study has shown the presence of myeloperoxidase in the glandular epithelial cells of the prostate (Roumeguere et al, 2012); however, the importance of this is unclear. The seminal plasma myeloperoxidase protein concentration was significantly different between the two groups (two-sample independent t-test with unequal variances).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Samples were divided around the median sperm count of 56.5 9 10 6 /mL of seminal plasma (below/equal median group n = 17; above median group n = 16). A recent study has shown the presence of myeloperoxidase in the glandular epithelial cells of the prostate (Roumeguere et al, 2012); however, the importance of this is unclear. The seminal plasma myeloperoxidase protein concentration was significantly different between the two groups (two-sample independent t-test with unequal variances).…”
Section: Discussionmentioning
confidence: 98%
“…This would preclude the prostate and seminal vesicles, where the presence of neutrophils is well established, as neutrophils from these glands should only come into contact with spermatozoa at the point of ejaculation (Aitken & Baker, 2013). A recent study has shown the presence of myeloperoxidase in the glandular epithelial cells of the prostate (Roumeguere et al, 2012); however, the importance of this is unclear. How and where inflammatory processes are able to impact on sperm health should be a focus for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few data are available about the origin and characterization of NSC in the equine. In dogs, squamous epithelial cells are observed in prostatic squamous metaplasia [27,28] and, recently, MPO has been observed in epithelial cells of human prostatic biopsies [29]. Further investigation in the equine should consider specific staining of genital tract biopsy samples to assess NSC anatomic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MPO immunostaining has been observed in horses NSC ) and in human prostatic cells (Roumeguere et al 2012). Recent studies (Ponthier et al 2013) confirmed that NSC undergoing cellular damage associated to freezing (Graham-Pole et al 1977;Wang et al 1997b) release MPO, somehow acting like sponges.…”
Section: Discussionmentioning
confidence: 87%